(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Green Human Resource Management [GHRM] practices are fast assuming importance in every sector today. This paper aims to understand the outcomes and antecedents of green HRM control at the firm level as well on individual level in the pharmaceutical sector. The study in particular, investigates the impact of Green HRM practices on environmental performance in the pharmaceutical sector, as the pharma industries play an important role in the economy of India. A quantitative study design was conducted using purposive sampling to select 189 respondents’ data. Findings suggest that green HRM practices have a strong impact on the performance of the firm. Key impact is observed in the cost-cutting, reduced carbon footprints, improved energy conservation and increased profitability of the pharmaceutical firms. The results provide a useful insight into green HRM for sustainable performance of the pharmaceutical firms.